Research progress of calcium carbonate nanomaterials in cancer therapy: challenge and opportunity - Liang, Tiantian; Feng, Zongqi; Zhang, Xiao; Li, Tianfang; Yang, Tingyu; Yu, Lan (Frontiers in Bioengineering and Biotechnology, 2023)
Cancer has keeping the main threat to the health of human being. Its overall survival rate has shown rare substantial progress in spite of the improving diagnostic and treatment techniques for cancer in recent years. Indeed, such classic strategies for malignant tumor as surgery, radiation and chemotherapy have been developed and bring more hope to the patients, but still been accompanied by certain limitations, which include the challenge of managing large wound sizes, systemic toxic side effects, and harmful to the healthy tissues caused by imprecise alignment with tumors in radiotherapy. Furthermore, immunotherapy exhibits a limited therapeutic effect in advanced tumors which is reported only up to 25% to 30%. The combination of nanomaterials and cancer treatment offers new hope for cancer patients, demonstrating strong potential in the field of medical research. Among the extensively utilized nanomaterials, calcium carbonate nanomaterials (CCNM) exhibit a broad spectrum of biomedical applications due to their abundant availability, cost-effectiveness, and exceptional safety profile. CCNM have the potential to elevate intracellular Ca2+ levels in tumor cells, trigger the mitochondrial damage and ultimately lead to tumor cell death. Moreover, compared with other types of nanomaterials, CCNM exhibit remarkable advantages as delivery systems owing to their high loading capacity, biocompatibility and biodegradability. The purpose of this review is to provide an overview of CCNM synthesis, focusing on summarizing its diverse roles in cancer treatment and the benefits and challenges associated with CCNM in cancer therapy. Hoping to present the significance of CCNM as for the clinical application, and summarize information for the design of CCNM and other types of nanomaterials in the future.